Development of ELIP to Assess Physical Literacy for Emerging Adults: A Methodological and Epistemological Challenge - Gandrieau, J; Schnitzler, C; Cairney, J; Keegan, R; Roberts, W M; Barnett, L M; Bentsen, P; Dudley, D A; Raymond Sum, K W; Venetsanou, F; Button, C; Turcotte, S; et al. (Research quarterly for exercise and sport, 2023)
Purpose: Following increased interest in physical literacy (PL), development of appropriate tools for assessment has become an important next step for its operationalization. To forward the development of such tools, the objective of this study was to build the foundations of the Évaluation de la Littératie Physique (ELIP), designed to help reduce existing tensions in approaches to PL assessment that may be resulting in a low uptake into applied settings. Methods: We followed two steps: (1) the development of the first version of ELIP by deploying a Delphi method (n = 30); and (2) the modification of items through cognitive interviews with emerging adults (n = 32). Results: The expert consensus highlighted four dimensions of PL to be assessed-physical; affective; cognitive; and social-with new perspectives, including a preference for broad motor tests over fitness. Conclusion: Results offer new insights into the assessment of emerging adults' PL, but ELIP still requires further work concerning validity, reliability, and sensitivity.
Keywords: Reproducibility of Results; Adult; dospělí; lidé; cvičení; zdravotní gramotnost; Humans; Exercise; reprodukovatelnost výsledků; Health Literacy